Perbedaan Kecemasan Ibu Hamil Trimester III yang Diberi Terapi Musik Mozart dan Terapi Murrotal Al-Qur’an - Dewi susanti; Mohamad Hasinuddin (Universitas Islam Madura, 2021)
Anxiety is a natural disorder of feeling characterized by a feeling of deep and sustained fear or concern. The results of preliminary studies that had been done in Polindes Pademawu Timur, there were 10 pregnant women experience anxiety. The purpose of this study was to analyze the differences between Mozart and murottal Al-qur'an music on the anxiety of pregnant women in the third trimester in the face of labor. This research used quasy experiment design. This design used a pretest and posttest design approach. The independent variables were mozart music therapy and murottal therapy of the Qur'an. The dependent variable was anxiety. The population is the third trimester pregnant women who got experience anxiety. The sample was taken as many as 18 pregnant women who were divided into mozart music therapy group and murottal Al-Qur'an therapy group. The instrument used was the questionnaire of hamilton rating scale for anxiety (HRSA). The results were analyzed using paired t-test on mozart music therapy and murottal therapy Al-Qur'an with value α = 0,05. The result of statistical test by used paired t-test in mozart music therapy group (ρ = 0,006). The result of statistic test using paired t-test in murottal therapy group of Al-Qur'an is (ρ = 0,000) meaning there was difference of pre patient's anxiety surgery between before and after mozart music therapy and murottal therapy of the Qur'an. The independent t-test showed the significance value ρ = 0.228. So it can be concluded that there was no difference in decreased anxiety of third trimester pregnant women between given mozart music therapy and murottal therapy Al-Qur'an. The results of this study is expected to get the experience of respondents and the application of mozart music therapy and murottal therapy Al-Qur'an in reducing anxiety in third trimester pregnant women.